Regional ocean biogeochemical modeling challenges for predicting the effectiveness of marine carbon dioxide removal - Ward, Nicholas D.; Hinson, Kyle E.; Pagès, Rémi; Cross, Jessica N.; Friedrichs, Marjorie A. M.; Hauri, Claudine; MacCready, Parker; Subban, Chinmayee V.; Xiong, Jilian; St-Laurent, Pierre; Yang, Zhaoqing (Frontiers in Climate, 2025)
Effectively scaling diverse marine carbon dioxide removal (mCDR) technologies from pilot-scale demonstrations to industrial-scale deployments requires a quantitative understanding of how much additional carbon a given deployment will sequester compared to a scenario with no mCDR intervention and the long-term durability of the stored carbon. Given the high environmental variability and vast size of the ocean carbon pool, observations alone cannot resolve the amount, rate, and fate of mCDR-associated carbon sequestration. Likewise, when conducting an mCDR deployment it is impossible to observe a counterfactual scenario with no mCDR deployment performed. For this reason, ocean biogeochemical models are expected to play a key role in advancing mCDR deployments by informing observational requirements, defining uncertainty envelopes, and ultimately verifying durable carbon sequestration. However, current models, which are designed to capture basic ocean processes, have limitations when being used for this new application—simulating perturbations to the ocean system ranging in scale. Here, we describe our perspective on the most critical ocean biogeochemistry model process representations that need to be refined or added to accurately simulate the impact of a subset of mCDR approaches on carbon uptake and ocean biogeochemistry.